Escritores investigadores: ¿literatura de investigación? - Paula Klein (Cuadernos LIRICO)
This article provides a panorama of the investigative literature produced in Río de la Plata over the last two decades, within the framework of the “documentary turn” that the literary field has continually undergone since the beginning of the 21st century. Within the range of contemporary factual writings, this investigative literary movement develops in the form of documentary narratives and archival fictions that aspire to reconstitute the space of the text as a democratic forum, a co-creation of knowledge that connects literature with the models and practices of investigative journalism and the social sciences. This article identifies a series of textual and paratextual parameters, narrative modes and literary positions of writer-researchers that appear as common denominators in the series of works discussed in this volume. Apart from the plurality of themes and their heterogeneous styles, these are texts that, through the use of documents, claim a high level of proximity to reality and consider the search for truth -factual and literary- to be their goal. Because of the new intersections and permeability of frontiers between fiction and nonfiction proposed by these texts, because of the political-social commitment they mobilize, and because of the relational force and pragmatic effects they aspire to produce in the real, their projects merit an analysis in aesthetic, ethical and political terms.